Arthroscopic undersurface rotator cuff repair versus conventional arthroscopic double-row rotator cuff repair – Comparable results at 2-year follow-up. (16th February 2018) - Ang, Benjamin Fu Hong; Chen, Jerry Yongqiang; Yeo, William; Lie, Denny Tijauw Tjoen; Chang, Paul Chee Cheng
Aim: The aim of our study is to compare the improvement in clinical outcomes after conventional arthroscopic double-row rotator cuff repair and arthroscopic undersurface rotator cuff repair. Method: A consecutive series of 120 patients who underwent arthroscopic rotator cuff repair was analysed. Sixty-one patients underwent conventional double-row rotator cuff repair and 59 patients underwent undersurface rotator cuff repair. Several clinical outcomes, including numerical pain rating scale (NPRS), constant shoulder score (CSS), Oxford shoulder score (OSS) and University of California Los Angeles shoulder score (UCLASS), were prospectively recorded by a trained healthcare professional preoperatively and at 3, 6, 12 and 24 months after surgery. Result: Comparing both groups, there were no differences in age, gender and preoperative NPRS, CSS, OSS and UCLASS. However, the tear size was 0.7 ± 0.2 (95% confidence interval (CI) 0.3–1.1) cm larger in the conventional group ( p = 0.002). There was no difference in the improvement of NPRS, CSS, OSS and UCLASS at all time points of follow–up, that is, at 3, 6, 12 and 24 months after surgery. The duration of operation was shorter by 35 ± 3 (95% CI 28–42) min in the undersurface group ( p < 0.001). Conclusion: Both arthroscopic undersurface rotator cuff repair and conventional arthroscopic double-row rotator cuff repair showed marked improvements in clinical scores when compared preoperatively, and there was no difference in improvements between both groups. Arthroscopic undersurface rotator cuff repair is a faster technique compared to the conventional arthroscopic double-row rotator cuff repair.